Chronic urticaria and drug hypersensitivity in children - Mastrorilli, Carlo; Bernardini, Roberto; Liotti, Lucia; Franceschini, Fabrizio; Crisafulli, Giuseppe; Caimmi, Silvia; Bottau, Paolo; Mori, Francesca; Cardinale, Fabio; Saretta, Francesca; Simeone, Giovanni; Bergamini, Marcello; et al. (Acta Biomedica Atenei Parmensis, 2019)
The cause of chronic urticaria remains often elusive. The association between chronic urticaria and intake of medications have been reported in children. However, the causative role of drugs has been rarely ascertained by onset of symptoms on drug provocation test. Chronic urticaria can be mediated by immunologic and nonimmunologic mechanisms. The diagnostic work-up of chronic urticaria includes a comprehensive evaluation of triggering factors such as drugs. A diagnosis is necessary in order to permit a safely administration of drugs in children with chronic urticaria.